2001
DOI: 10.1093/jhered/92.6.490
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial 16S rRNA Sequence Diversity of Hominoids

Abstract: We determined nucleotide sequences of the 16S rRNA gene of mitochondrial DNA (mtDNA) (about 1.6 kb) for 35 chimpanzee, 13 bonobo, 10 gorilla, 16 orangutan, and 23 gibbon individuals. We compared those data with published sequences and estimated nucleotide diversity for each species. All the ape species showed higher diversity than human. We also constructed phylogenetic trees and networks. The two orangutan subspecies were clearly separated from each other, and Sumatran orangutans showed much higher nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…They would occasionally substitute to G, as they did in the human lineage, and transiently become G→A hypermutable until state A fixes again. This simple process might partly explain the decrease of polymorphism co-occurrence with species divergence: The mutation rate of a site simply varies when it substitutes from a mu- Noda et al (2001). This site might correspond to a unidirectional G→A hot spot, hypermutable only when in state G. Site 3010, finally, shows state G in four of the five species surveyed by Noda et al (2001) but appears monomorphic in these species.…”
Section: Discussionmentioning
confidence: 99%
“…They would occasionally substitute to G, as they did in the human lineage, and transiently become G→A hypermutable until state A fixes again. This simple process might partly explain the decrease of polymorphism co-occurrence with species divergence: The mutation rate of a site simply varies when it substitutes from a mu- Noda et al (2001). This site might correspond to a unidirectional G→A hot spot, hypermutable only when in state G. Site 3010, finally, shows state G in four of the five species surveyed by Noda et al (2001) but appears monomorphic in these species.…”
Section: Discussionmentioning
confidence: 99%
“…''There are several competing hypotheses on the phylogenetic relationships of species within subgenus Hylobates y these gibbon species are closely related, hybridization is possible, and this may be the source of incongruent phylogenetic relationships y'' (Noda et al, 2001). Indeed, the expectation of a close evolutionary and genetic relationship between species of Hylobates (i.e.…”
Section: Hominoids/gibbonsmentioning
confidence: 99%
“…For example, an analysis of sequence variation in the mitochondrial 16S rRNA gene resulted in the paraphyletic placement of one individual of H. pileatus, of the subgenus Hylobates, with H. concolor, subgenus Nomascus (Noda et al, 2001). In addition, within the ''monophyletic'' subgenus Hylobates clade, individuals of H. klossii were more closely related to individuals of H. agilis or H. lar than to other gibbons that morphologically resemble H. klossii (Noda et al, 2001). In contrast, Hayashi et al (1995) had previously found a monophyletic relationship of individuals of H. lar and H. klossii.…”
Section: Hominoids/gibbonsmentioning
confidence: 99%
See 2 more Smart Citations